Redesign, optimization and validation of keyseat - Muttaqin, Hilman (2008)
Function of keyseat is to lock between main component and sub component like shaft and gear in transmission. Keyseat as one part of moving machine’s component need a precision calculation in design, as that reason this project studied about analysis and optimization of design from two dimension model to solid modeling model. Objectives of this project are to redesign a keyseat from the original design, optimize the parameter values and to validate the value using calculation and simulation concept. The original design was taken from anonymous design, and a new keyseat design was made under reflection from the literature reviews. This project have four phases; the first phase is redesigned the original design that add two keyseat into two location, second phase is analyzed the new design with mathematical analysis to identify the optimization of this new design, third phase is built solid modeling by using Computer-Aided Design (CAD) and then simulated by Computer-Aided Manufacturing (CAM), the last phase was made real manufacturing by using CNC machine that drive with G-code that generated from CAM program. Methodology that was used is analysis variable method; variables which affect the value of the objective function, in the manufacturing problem, the variables might include the amounts of different resources used or the time spent on each activity. As the conclusion, redesign and optimization of keyseat is usable in all of shaft in machining part to minimize the failure and minimize the decrease a torque.